2007
DOI: 10.1111/j.1742-4658.2007.06161.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcite‐specific coupling protein in barnacle underwater cement

Abstract: Sessile organisms are destined for attachment to various materials in water. Because gregariousness is essential for them, the opportunity to attach to a calcific exoskeleton of the same kind is necessarily favored. Thus, calcific material is one of the frequent foreign materials for attachment in the molecular system of the holdfast.The barnacle is a unique sessile crustacean. Once the larva has settled on the foreign substratum, it metamorphoses, calcifying the outer shell at the periphery and base, and perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 33 publications
(54 reference statements)
10
86
0
Order By: Relevance
“…Additionally, phosphoproteins are important to the development of extracellular matrices and the transition to calcification (Borbas et al, 1991;Arias et al, 1993;George et al, 1993;Fernández et al, 2002;Johnstone et al, 2015a). Barnacle baseplate and shell biomineralization involve an initial organic matrix in which calcite crystals form (Fernández et al, 2002;Mori et al, 2007;Lewis et al, 2014), with the potential for involvement of calcite-carrying hemocytes, as seen in oyster calcification (Mount et al, 2004;Zhang et al, 2013;Johnstone et al, 2015;Li et al, 2016). Estimates of barnacle hemocyte concentrations are 1.7×10 2 cells μl −1 hemolymph, mostly composed of hyaline cells and some semigranular cells (Waite and Walker, 1988;Dickinson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, phosphoproteins are important to the development of extracellular matrices and the transition to calcification (Borbas et al, 1991;Arias et al, 1993;George et al, 1993;Fernández et al, 2002;Johnstone et al, 2015a). Barnacle baseplate and shell biomineralization involve an initial organic matrix in which calcite crystals form (Fernández et al, 2002;Mori et al, 2007;Lewis et al, 2014), with the potential for involvement of calcite-carrying hemocytes, as seen in oyster calcification (Mount et al, 2004;Zhang et al, 2013;Johnstone et al, 2015;Li et al, 2016). Estimates of barnacle hemocyte concentrations are 1.7×10 2 cells μl −1 hemolymph, mostly composed of hyaline cells and some semigranular cells (Waite and Walker, 1988;Dickinson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The protein contents of barnacle cement has been the topic of considerable research as of late (Kamino 2001;Mori et al 2007;Urushida et al 2007;Kamino 2008;Dickinson et al 2009) yet few cement proteins have been added to the database (19kDa, 20kDa, and 100kDa as well as insoluble partial peptide fractions). Although many were collected from a different, though similar species, Megabalanus rosa, we were consequently hopeful in identifying similar cement polymers on the basis that partial sequence data may be used.…”
Section: Discussionmentioning
confidence: 99%
“…Barnacle cement is primarily composed of proteins ranging from 3kDa to upwards of 160kDa with proteins between 50kDa and 100kDa being the most prominent in terms of volume (Kamino et al 1996;Naldrett and Kaplan 1997). Mori et al (2007) identified a calcium coupling protein (20kDa) only found within the primary cement of Megabalanus rosa suggesting cement-specific proteins such as this may relate to the adhesive's incredible ability to cure underwater. Changes in concentration or appearance of these proteins may affect cement tenacity.…”
Section: Ecophenotypic Response Of Cement To Temperaturementioning
confidence: 99%
See 2 more Smart Citations